Media Sosial dan Aktivisme Digital Perempuan: Analisis Wacana #Ibutunggalmelawan di Instagram - Dwityas, Nindyta Aisyah; Marta, Rustono Farady; Briandana, Rizki (Jurnal Komunikasi, 2024)
Digital activism, commonly referred to as online activism, is the practice of using electronic communication tools as a type of activism aimed at fostering the development of community movements. Digital activism is connected to online discourse through various mechanisms, including social media platforms, connectivity actions and the discursive construction of digital technology.  The purpose of this study is to examine the discourse that is growing in the comments section of the online petition content for the #MotherSingleMelawan on the Instagram account @changeorg_id, as well as the signs of female digital activism that are emerging. Marie-Anne Paveau pioneered the qualitative discourse analysis research methodology, which is particularly relevant when applied to online communication. The results of the research show that women's digital activism in the comments column of the #SingleMotherMelawan online petition consists of four main discourse themes, namely; 1) the discourse of belief-based gender oppression, 2) the discourse of gender relations in parental relations, 3) the discourse of justice for victims of gender-based violence, 4) the discourse of discrimination against single mothers.